The sialidase inhibitor 2,3-dehydro-2-deoxy-N-acetylneuraminic acid is a glucose-dependent potentiator of insulin secretion - Minami, Akira (Sci Rep, 2020)
Sialidase cleaves sialic acid residues from a sialoglycoconjugate: oligosaccharides, glycolipids and glycoproteins that contain sialic acid. Histochemical imaging of the mouse pancreas using a benzothiazolylphenol-based sialic acid derivative (BTP3-Neu5Ac), a highly sensitive histochemical imaging probe used to assess sialidase activity, showed that pancreatic islets have intense sialidase activity. The sialidase inhibitor 2,3-dehydro-2-deoxy-N-acetylneuraminic acid (DANA) remarkably enhances glutamate release from hippocampal neurons. Since there are many similar processes between synaptic vesicle exocytosis and secretory granule exocytosis, we investigated the effect of DANA on insulin release from β-cells. Insulin release was induced in INS-1D cells by treatment with 8.3 mM glucose, and the release was enhanced by treatment with DANA. In a mouse intraperitoneal glucose tolerance test, the increase in serum insulin levels was enhanced by intravenous injection with DANA. However, under fasting conditions, insulin release was not enhanced by treatment with DANA. Calcium oscillations induced by 8.3 mM glucose treatment of INS-1D cells were not affected by DANA. Blood insulin levels in sialidase isozyme Neu3-deficient mice were significantly higher than those in WT mice under ad libitum feeding conditions, but the levels were not different under fasting conditions. These results indicate that DANA is a glucose-dependent potentiator of insulin secretion. The sialidase inhibitor may be useful for anti-diabetic treatment with a low risk of hypoglycemia.